The Influence of The Classroom Environment on Student Motivation in The Penjas Learning Process - Syahruddin, Syahruddin; Raharja, Andri Tria (Journal of Educational Sciences, 2025)
This study aims to analyze the influence of the classroom environment on students' learning motivation in the Physical Education learning process. A comfortable and conducive classroom environment is believed to be able to increase students' enthusiasm for learning, especially in the Penjas subject which involves physical activity. This study uses a quantitative method with a survey approach. Based on the results of quantitative research, data processing and analysis show that the classroom environment and the role of the teacher as a whole are in the sufficient category; the classroom environment and the role of the teacher as a whole are in the neutral category; the school and the role of the teacher as a whole have a positive effect on students' learning motivation; the classroom environment and the role of the teacher as a whole have a positive effect on students' learning motivation; and the role of the teacher as a whole can increase students' learning motivation.